Attenuation of cartilage degeneration by calcitonin gene‐related paptide receptor antagonist via inhibition of subchondral bone sclerosis in osteoarthritis mice. Issue 7 (12th January 2016) - Nakasa, Tomoyuki; Ishikawa, Masakazu; Takada, Tsuyoshi; Miyaki, Shigeru; Ochi, Mitsuo
ABSTRACT: Osteoarthritis (OA) is a progressive joint disorder which affects cartilage and subchondral bone. Calcitonin gene‐related peptide (CGRP) plays a role in bone metabolism. The purpose of this study is to examine the therapeutic effect of the blocking CGRP on OA progression in mice by inhibition of subchondral bone sclerosis. OA was induced by the resection of the medial meniscotibial ligament of the knee in C57/BL6 mice. An intraperitoneal injection of the CGRP receptor antagonist (BIBN4096) was administered after OA surgery. At 1, 4, and 8 weeks after injection, histological analysis were performed. In vitro, the effect of CGRP and BIBN4096 on osteogenesis and osteoclastogenesis was analyzed. BIBN4096 could prevent cartilage degeneration and subchondral bone sclerosis. The OARSI score in the BIBN4096 group was significantly lower than that in the control. In vitro, CGRP up regulated osteocalcin expression, but its expression was down regulated by BIBN4096. CGRP inhibited osteoclastogenesis of raw 267.4 cells, but its effect was reduced by the addition of BIBN4096.The current study showed that subchondral bone sclerosis and increasing expression of CGRP occurs in the early phase of OA in relation to cartilage degeneration, and that BIBN4096 could effectively attenuate OA progression. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1177–1184, 2016.